Investigating Pre-Service Teachers’ Emotions Attributions in Teaching Practicum: Lessons Learned from Indonesian Teacher Education - Nur Waqiah, Siti; Nurhadi, Kardi; Yulianawati, Ida (International Journal of Language Teaching and Education, 2021)
Driven by Mendez-Lopez (2020) on the emotion factors which impact to pre-service teachers enacting the teaching practicum, this research report how pre-service teachers’ expressed their emotions attributions in teaching practice. Grounded in narrative inquiry, this research provides investigation on pre-service teachers’ emotions attributions in teaching practice while they were doing the teaching and learning activity with students in the classroom. Three female pre-service teachers from an Indonesian teacher education are recruited in this research voluntarily. The data were collected through semi-structured interview. The data was analyzed by using qualitative content analysis (Patton, 2002). The findings indicated that pre-service teachers need to do positive emotions attributions toward students’ behavior. And, it allows pre-service teachers to manage their emotions during English Teaching practice wisely. Then, pre-service teachers can realize about the importance of improving their teaching skills professionally through teaching practice. Thus, pre-service teachers also can add the belief about how to carry out successful teaching and learning activities during English teaching practice as the lesson for them in the future. This study implied that pre-service teachers must be able to attribute their emotions in teaching wisely to increase students' motivation to learn English situated in Indonesian teacher education.